Mengatasi Problematika Pembelajaran Bahasa Arab Dengan Pendekatan Game Based Learning Dalam Penguasaan Tata Bahasa Arab - Haitsumakunti, Ittaqi; Faizi, Ahmad; Aisyah, Siti (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
Arabic language learning, particularly in the aspects of grammar (nahwu and sharf), often faces challenges such as monotonous teaching methods, low student motivation, and limited learning media. These difficulties hinder students’ mastery of Arabic grammar. This article explores Game-Based Learning (GBL) as an innovative approach to enhance the effectiveness of Arabic grammar instruction. GBL incorporates game elements, such as challenges, competition, and rewards, to create an interactive and enjoyable learning environment. The implementation strategies discussed include the use of digital applications, chain word games, Arabic crossword puzzles, and grammar cards. This approach has proven effective in increasing students' motivation, engagement, and understanding of Arabic grammar through contextual and engaging learning experiences. With adequate support, GBL can be an effective alternative to address challenges in Arabic grammar instruction, while motivating students to be more active and proficient in using the language. This article serves as an essential reference for developing more relevant, creative, and tailored teaching methods for today’s digital generation.